Myosin light chain phosphorylation enhances contraction of heart muscle via structural changes in both thick and thin filaments - Kampourakis, Thomas (Proc Natl Acad Sci U S A, 2016)
Contraction of heart muscle is triggered by calcium binding to the actin-containing thin filaments but modulated by structural changes in the myosin-containing thick filaments. We used phosphorylation of the myosin regulatory light chain (cRLC) by the cardiac isoform of its specific kinase to elucidate mechanisms of thick filament-mediated contractile regulation in demembranated trabeculae from the rat right ventricle. cRLC phosphorylation enhanced active force and its calcium sensitivity and altered thick filament structure as reported by bifunctional rhodamine probes on the cRLC: the myosin head domains became more perpendicular to the filament axis. The effects of cRLC phosphorylation on thick filament structure and its calcium sensitivity were mimicked by increasing sarcomere length or by deleting the N terminus of the cRLC. Changes in thick filament structure were highly cooperative with respect to either calcium concentration or extent of cRLC phosphorylation. Probes on unphosphorylated myosin heads reported similar structural changes when neighboring heads were phosphorylated, directly demonstrating signaling between myosin heads. Moreover probes on troponin showed that calcium sensitization by cRLC phosphorylation is mediated by the thin filament, revealing a signaling pathway between thick and thin filaments that is still present when active force is blocked by Blebbistatin. These results show that coordinated and cooperative structural changes in the thick and thin filaments are fundamental to the physiological regulation of contractility in the heart. This integrated dual-filament concept of contractile regulation may aid understanding of functional effects of mutations in the protein components of both filaments associated with heart disease.